Are board games useful for people with dementia? A preliminary study for a non-pharmacological intervention - Guardabassi, Veronica; Maranesi, Alessandro; Di Massimo, Marta; Manoni, Evelyn; Cirilli, Elisa; Nicolini, Paola (Frontiers in Psychology, 2025)
IntroductionThe diagnosis of dementia presents a serious public health concern and a challenge for the entire scientific community. Among the potential lines of intervention, board games can be considered a non-pharmacological strategy. This study aimed to explore the potential of board games as a group-based intervention to support cognitive stimulation and psychological well-being in people with dementia.MethodsThis study included 36 older people diagnosed with dementia (Mage = 86.13; SD = 6.94; MMMSE = 18.82, SD = 2.96). Participants performed verbal working memory, verbal fluency and denomination tasks at the beginning of the project (T1), played with board games with their facilities’ professionals over a month (S1), and, at the end, they did a parallel form of the initial cognitive tasks (T2). Then, they played with their games’ conductors for a further 2 months (S2), and at the end of this period (T3), they performed the initial cognitive tasks. The research team observed participants’ level of well-being during S1, and facility professionals completed a questionnaire at T1, T2, and T3 to provide information about participants’ symptoms of depression (T1 and T3) and their point of view on board game activity (T2 and T3).ResultsThe results showed that cognitive functions do not increase over time [F (2, 32) = 2.54, p = 0.095, η2 = 0.145]. However, there was a significant change after the first month (p = 0.029). Specifically, the verbal fluency improved from T1 to T2 (p = 0.042). In addition, the results indicated that the level of well-being observed during board game activities was higher than the level of discomfort [F (1, 35) = 133.69, p > 0.001, η2 = 0.876]. Professionals’ responses to open-ended questions about cognitive functioning and psychological well-being corroborated the findings. No changes in depression symptoms were found [F (3, 19) = 2.39, p = 0.105, η2 = 0.297].DiscussionThe results of this study suggest that board games can be explored further as a non-pharmacological intervention for groups of older adults diagnosed with dementia, as favorable outcomes were observed in terms of cognition and well-being. Theoretical implications, research directions, and professional perspectives were also discussed.